Lymphoid cells transformed by Abelson virus require the v-abl protein-tyrosine kinase only during early G1. - Chen, Y Y (1992)
Cells infected with temperature-sensitive transformation mutants of the Abelson murine leukemia virus express low levels of kinase activity at the nonpermissive temperature, causing transformed pre-B cells to die under these conditions. Examination of cell cycle profiles of such populations prior to cell death reveals that the cells accumulate in the G1 phase of the cell cycle. Following G1 arrest, the cells die via apoptosis, an active process of cell elimination. Cell synchronization and temperature-shift experiments show that G1 arrest reflects the requirement for a functional v-abl protein during early G1 and that the molecule is not required at other phases of the cell cycle. These data indicate that the substrate(s) critical to v-abl-mediated transformation is involved in regulating G1 transit and that these interactions are dominant over all other changes required for the multistep process that results in the fully malignant phenotype associated with v-abl expression in lymphoid cells.